On the (Non‐)equivalency of monopolar and bipolar settings for deep brain stimulation fMRI studies of Parkinson's disease patients. Issue 6 (15th December 2018) - Hancu, Ileana; Boutet, Alexandre; Fiveland, Eric; Ranjan, Manish; Prusik, Julia; Dimarzio, Marisa; Rashid, Tanweer; Ashe, Jeffrey; Xu, David; Kalia, Suneil K.; Hodaie, Mojgan; Fasano, Alfonso; et al.
Abstract : Background: The majority of Parkinson's disease patients with deep brain stimulation (DBS) use a monopolar configuration, which presents challenges for EEG and MRI studies. The literature reports algorithms to convert monopolar to bipolar settings. Purpose/Hypothesis: To assess brain responses of Parkinson's disease patients implanted with DBS during fMRI studies using their clinical and presumed equivalent settings using a published conversion recipe. Study Type: Prospective. Subjects: Thirteen DBS patients. Field Strength/Sequence: 1.5T and 3T, fMRI using gradient echo‐planar imaging. Assessment: Patients underwent 30/30sec ON/OFF DBS fMRI scans using monopolar and bipolar settings. To convert to a bipolar setting, the negative contact used for the monopolar configuration remained constant and the adjacent dorsal contact was rendered positive, while increasing the voltage by 30%. fMRI activation/deactivation maps and motor Unified Parkinson's Disease Rating Scale (UPDRS‐III) scores were compared for patients in both configurations. Statistical Tests: T ‐tests were used to compare UPDRS scores and volumes of tissue activated (VTA) diameters in monopolar and bipolar configurations. Results: The patterns of fMRI activation in the monopolar and bipolar configurations were generally different. The thalamus, pallidum, and visual cortices exhibited higher activation using the patient's clinical settings than the presumed equivalent settings. VTA diameters were lower (7 mm vs. 6.3 mm, P = 0.047) and UPDRS scores were generally higher in the bipolar (33.2 ± 16) than in the monopolar configuration (28.3 ± 17.4), without reaching statistical significance ( P > 0.05). Data Conclusion: Monopolar and bipolar configurations result in different patterns of brain activation while using a previously published monopolar–bipolar conversion algorithm. Clinical benefits may be achieved with varying patterns of brain responses. Blind conversion from one to the other should be avoided for purposes of understanding the mechanisms of DBS. Level of Evidence: 1 Technical Efficacy: Stage 1 J. Magn. Reson. Imaging 2018.